PENGARUH TRUST DAN COMMITMENT TERHADAP KEPUASAN DAN LOYALITAS PADA LEMBAGA BIMBINGAN BELAJAR NEUTRON KOTA MALANG - A. Nor Maulidi; N. Rachma; Afi Rahmat (E-JRM : Elektronik Jurnal Riset Manajemen)
AbstractThis study aims to analyze the direct influence and indirect influence of Trust and Commitment on Loyalty through satisfaction as an intervening variable in the Malang City Neutron Tutoring Institute. This type of research is an explanatory research type using a quantitative approach. This research was conducted by distributing questionnaires to 76 respondents who were participants in the Neutron tutoring institution. The sample technique used in this study is purposive sampling. The analysis technique used in this study is path analysis.The results of this study indicate that Trust and Commitment directly and significantly affect Loyalty. Trust and commitment directly and significantly affect satisfaction. Satisfaction directly and significantly affects Loyalty. And Trust and Commitment directly and significantly affect Loyalty through satisfaction as an intervening variable.Keyword: Trust, Commitment, Satisfaction, and Loyalty